RANCANG BANGUN RT/RW INFORMATION SYSTEM BERBASIS MOBILE PADA PERUMAHAN SWAN REGENCY - Syahrizal Setia Wicaksana; Anjik Sukmaaji; Agus Dwi Churniawan (Jurnal Sistem Informasi Universitas Dinamika, 2022)
Swan Regency Housing is a housing estate located in Sedati, Sidoarjo, East Java. In Swan Regency Housing there are also several RT and RW who manage and supervise the community in Swan Regency Housing. Therefore, there are also various policies that have been previously offered for the welfare of the surrounding community, for example there are various dues for cleanliness, security, community facilities and for village inventory equipment. Therefore ideally there will be one person who will take care of all things financially commonly referred to as treasurer. In general the treasurer is the one who takes care of all the money in and out. According to (PERDA KAB. SIDOARJO No. 11, 2002) Regional Financial Management is carried out in an orderly manner, complying with the prevailing Laws, efficient, effective, transparent and responsible by taking into account the principles of fairness and propriety. However, in the implementation of financial management in Swan Regency Housing has not been transparent, causing various problems such as residents wondering about the money that has been paid, as well as the many questions about finances when the village meeting is being held.With the problems described above, the solution offered to solve the problem is the making of a mobile-based RT/RW information system that is expected to solve the problem that has been described. The app is also expected to be easy to access, therefore a popular and widely used mobile selection is chosen for this app. In this app there is also a financial report feature so that the public knows all the money that has been paid is used for what directly. The report feature is also intended to make it easier for the treasurer to create the desired report.Based on the results of the trial can show that the application can help financial management activities and residents, the quick and easy access of this application, and the ease of the creation of RT and RW financial reports on Swan Regency Housing.